2003
DOI: 10.1111/j.1346-8138.2003.tb00378.x
|View full text |Cite
|
Sign up to set email alerts
|

Klippel‐Trenaunay Syndrome with a Life‐Threatening Thromboembolic Event

Abstract: Klippel-Trenaunay syndrome is a congenital disorder characterised by the triad of cutaneous vascular nevi, soft tissue or bony hypertrophy, and varicose veins or venous malformations involving one or more extremities. An incidence of venous thromboembolism of up to 22% has been reported in this disorder. Also reported but rare is the development of trophic changes. Herein, we report the case of a male with Klippel-Trenaunay syndrome, deep vein thrombosis, venous ulceration, and death due to recurrent pulmonary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 14 publications
2
18
0
2
Order By: Relevance
“…Paradoxically, KTS patients are also at risk of thromboembolic complications, with a reported incidence of venous thromboembolism as high as 22%. 12 Deep vein hypoplasia of the lower extremities, along with the increased blood volume of pregnancy and relative obstruction of venous return by the gravid uterus, can lead to edema and vascular sludging. Additionally, as the varicosities are at risk of minor trauma, and most KTS patients would be expected to be in a hypercoagulable state secondary to pregnancy, the classic predisposing factors for venous thrombosis -stasis, hypercoagulability, and vascular injury -are often met in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Paradoxically, KTS patients are also at risk of thromboembolic complications, with a reported incidence of venous thromboembolism as high as 22%. 12 Deep vein hypoplasia of the lower extremities, along with the increased blood volume of pregnancy and relative obstruction of venous return by the gravid uterus, can lead to edema and vascular sludging. Additionally, as the varicosities are at risk of minor trauma, and most KTS patients would be expected to be in a hypercoagulable state secondary to pregnancy, the classic predisposing factors for venous thrombosis -stasis, hypercoagulability, and vascular injury -are often met in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the literature showed that Klippel-Trénaunay syndrome has been associated with venous thromboembolism in 8% to 22% of the cases [3][4][5][6][7][8][9]. The underlying mechanism of hypercoagulability in vascular malformations is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Des cas d'embolies pulmonaires sévères ont été décrites chez l'adulte [8][9][10]. Les épisodes d'embolies pulmonaires répétés peuvent également entraîner des hypertensions artérielles pulmonaires chroniques.…”
Section: Autresunclassified